Role of Epidural Steroid Injection in Lumbar Spinal Stenosis—A Randomized Controlled Trial - Mohit Kishore Srivastava; Anil Kumar Gupta; Sudhir R. Mishra; Dileep Kumar; Bal Krishna Ojha; Ganesh Yadav (Indian Journal of Neurosurgery)
Background Degenerative lumbar spinal stenosis (DLSS) is an important cause of pain and disability among the elderly and common indication for spinal surgery. However, due to age-related comorbidities, it becomes difficult for elderly patients of DLSS to immediately go for operative treatment. Caudal epidural steroid injection (CESI) can be an effective procedure for a selected group of patients who have chronic function-limiting lower back and lower extremity pain secondary to DLSS. The aim of this study was to compare the effects of CESI with physical therapy in patients afflicted with DLSS. Materials and Methods It is a single center, open-label randomized controlled trial conducted in department of Physical Medicine and Rehabilitation at a tertiary care center of northern India from January 2016 to August 2017 among DLSS patients. Trial was registered under the clinical trial registry of India. Patients were randomized in two groups–32 in intervention group A (CESI with local anesthetic and physical therapy) and 32 in control group B (physical therapy alone). Outcome measures were numerical pain rating scale (NPRS), Oswestry disability index (ODI), and mean claudication distance (MCD) at 3, 6, 12, and 24 weeks. Results NPRS and ODI showed significant improvement at 3, 6, 12, and 24 weeks (group A >> group B). Improvement in MCD was seen at each follow-up from baseline (group A >> group B). Conclusion Caudal epidural steroid administration can ameliorate pain, disability and claudication distance in DLSS patients, which provides them a window period for further definitive management.